2015
DOI: 10.1111/tmi.12467
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' adherence to acute coronary syndrome prescribing guidelines in Vietnamese hospital practice: a cross‐sectional study

Abstract: In general, physicians closely adhered to ACS prescribing guidelines in Vietnamese hospital practice. Prescribing of beta blockers and clopidogrel loading doses was probably suboptimal. Why patients do not complete treatment needs to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(83 reference statements)
2
7
0
1
Order By: Relevance
“…A retrospective cohort study of 202 patients with ACS in China demonstrated that patients were more likely to achieve LDL-C goal if they were receiving ezetimibe plus statin (69.1%, P = 0.007) or intensive statin therapy (67.9%, P = 0.047) compared with moderate-intensity statin (46.9%) [31]. Consistent results were reported for a prospective cohort study in 84 Chinese patients with [109,110] 90.7 [110] 100 [89] ACS acute coronary syndrome a For studies that recorded percentage statin use over more than 1 time period, the data for the most recent time period are presented [34]. Rates of statin use were similar in the three groups at discharge (96-98%) and at 1 year post ACS (93-96%); however, goal attainment rates differed between the groups (P \ 0.001); 23% of patients in whom FH was unlikely achieved their LDL-C goal, compared with 13% and 12% of patients with probable and possible FH, respectively.…”
Section: Use Of High-intensity Lmt Statin Therapysupporting
confidence: 60%
“…A retrospective cohort study of 202 patients with ACS in China demonstrated that patients were more likely to achieve LDL-C goal if they were receiving ezetimibe plus statin (69.1%, P = 0.007) or intensive statin therapy (67.9%, P = 0.047) compared with moderate-intensity statin (46.9%) [31]. Consistent results were reported for a prospective cohort study in 84 Chinese patients with [109,110] 90.7 [110] 100 [89] ACS acute coronary syndrome a For studies that recorded percentage statin use over more than 1 time period, the data for the most recent time period are presented [34]. Rates of statin use were similar in the three groups at discharge (96-98%) and at 1 year post ACS (93-96%); however, goal attainment rates differed between the groups (P \ 0.001); 23% of patients in whom FH was unlikely achieved their LDL-C goal, compared with 13% and 12% of patients with probable and possible FH, respectively.…”
Section: Use Of High-intensity Lmt Statin Therapysupporting
confidence: 60%
“…Thirdly, we could not assess conditions that contraindicated the use of DAPT, anticoagulants, and statins, such as history of intolerance, active gastrointestinal bleeding, or active liver disease [20,[43][44][45][46]. The prevalence of conditions that contraindicated the use of these medications in STEMI patients has also rarely been reported in previous studies.…”
Section: Limitationsmentioning
confidence: 94%
“…We have described the criteria to be eligible for being prescribed the medications elsewhere. 17 Briefly, patients eligible for being prescribed an antiplatelet agent, a beta-blocker or a statin were all patients who did not have contraindications to the medications. Patients eligible for being prescribed an ACEI/ARB were patients with prior heart failure, an LVEF<40%, diabetes mellitus or hypertension, and no contraindications to the medication.…”
Section: Methodsmentioning
confidence: 99%
“… 14–16 In fact, in-hospital guideline adherence for patients with ACS in Vietnam was suboptimal. 17 Prescribing of guideline-recommended medications has been shown to reduce both in-hospital and postdischarge morbidity and mortality. 18–22 The impact of guideline adherence on mortality of patients with ACS during hospitalisation has been determined previously.…”
Section: Introductionmentioning
confidence: 99%